2014
DOI: 10.1087/20140203
|View full text |Cite
|
Sign up to set email alerts
|

How research funders can finance APCs in full OA and hybrid journals

Abstract: ABSTRACT. Open access (OA) publishing is steadily growing in both full

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 6 publications
2
51
0
3
Order By: Relevance
“…However, all of these authors agree that the average APC for OA articles published in hybrid journals is significantly higher than the average APC for articles published in Gold OA journals (see also Björk and Solomon, 2014b). The general consensus seems to be that there is currently no properly functioning market for the cost of APCs in hybrid journals.…”
Section: Comparing Costs Associated With Open and Paywalled Access Inmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all of these authors agree that the average APC for OA articles published in hybrid journals is significantly higher than the average APC for articles published in Gold OA journals (see also Björk and Solomon, 2014b). The general consensus seems to be that there is currently no properly functioning market for the cost of APCs in hybrid journals.…”
Section: Comparing Costs Associated With Open and Paywalled Access Inmentioning
confidence: 99%
“…The leading journals with established brand names and high Impact Factors may charge higher than average sums, and there are clear incentives for researchers to try to publish in these journals. In addition, the hybrid journals tend to charge higher APCs than Gold OA journals (Björk & Solomon, 2014b). On the other hand, there are also new emerging OA business models which may lead to diminished costs.…”
Section: Comparing Costs Associated With Open and Paywalled Access Inmentioning
confidence: 99%
“…Morrison (2013), considering library expenditures on scholarly journals globally, concluded that these funds are more than the cost for a fully open access journal system. Björk and Solomon (2014), for example, proposed ways research funders could contribute to paying APCs and also influence the OA APC market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…5 The survey asked the librarians what involvement they had with payment, and from where the APCs were sourced. Multiple answers were allowed in recognition of the mix of payment processes currently operations.…”
Section: Funding Sources For Open Access Publishingmentioning
confidence: 99%